Diagnóstico situacional y propuestas de mejora para el área de almacén y compras de una empresa de servicios - Baca Izquierdo, Carla (2009)
This work is performed in the warehouse and Shopping Area from a service company, which has serious drawbacks in the development of their daily activities, based on problems such as obsolete and defective items, disorder, long-haul equipment, among others. First a situational analysis is done to identify improvement opportunities, uses tools such as ABC analysis, demand studies, inventory turnover and inventory turnover in days; the encountered problems are exposed and with the Cause – Effect diagram, the possible causes that affect the occurrence of such problems are identified. It then uses the criticality analysis to prioritize the causes, and discusses its feasibility, through an Impact-Feasibility analysis, improvement opportunities are selected with the implementation of Strategic Prioritization Matrix. Finally proposals of improvement are made for each opportunity, examines the impact of each proposal to establish priorities for the implementation, and design a schedule of activities which indicates: the responsible, the estimated duration of each activity and the necessary resources needed for implementation.